PROFIL TINGGI BADAN, DAYA LEDAK (POWER) OTOT TUNGKAI, KELINCAHAN (AGILITY) DAN DAYA TAHAN (ENDURANCE) ATLET BULUTANGKIS PB SURYA BAJA SURABAYA USIA 12-16 TAHUN - ALSYAHBANA, MARDHA (Jurnal Kesehatan Olahraga, 2014)
AbstractPB Surya Baja Surabaya is an achievers badminton club for three. The researchers wanted to examine thephysical condition supporting factors of badminton athletes. The purpose of this research is, 1. To find empiricalinformation about the heights profile of the PB Surya Baja Surabaya Badminton Athletes Aged 12-16 Years, 2. Tofind empirical information about the legs muscles explosive power profile of PB Surya Baja Surabaya BadmintonAthletes Aged 12-16 Years, 3. To find empirical information about the agility profile of the PB Surya Baja SurabayaBadminton Athletes Aged 12-16 Years, 4. To find empirical information about the resistance profile of the PB SuryaBaja Surabaya Badminton Athletes Aged 12-16 Years, 5. To find out the achievements profile of the PB Surya BajaSurabaya Badminton Athletes Aged 12-16 Years. This study only focused on the aspect of leg muscle explosivepower, agility, endurance, and height of PB Surya Baja Surabaya Badminton Athletes Aged 12-16 Years.This research is descriptive quantitative study with sample amount by 40 athletes. Data analysis techniqueused is a quantitative analysis. The results obtained from 40 athletes PB Surya Baja Surabaya aged 12-16 years,height measurement obtained from the mean value of 1.585 m with a range of 1.30 m to 1.72 m, body massmeasurements obtained from the mean value of 47.875 kg with a range of 31 kg to 72 kg, height jump obtained fromthe mean value 0.529 m with a range of 0.30 m to 0.65 m, leg muscle explosive power measurements obtained fromthe mean value of 910.413 watts, with a range of 519.222 watts to 1782.568 watts, agility measurement obtainedmean value of 59.850 points, with a range of 55 points to 65 points, the measurement of endurance mean valuesobtained 38.865 ml/kg/min with a range of 30.6 ml/kg/min to 49 ml/kg/min.The conclusion of this study is 1. Height the highest athlete is 1.72 m, height the shortest athletes is 1.30 mand the mean height 1.585 m, 2. The test results of measurement of legs muscles explosive power including in thecategories above average, based on the value of Mean 910.413 watts, 3. The results of the test agility belongs to thecategory below average, based on the mean value of 59.850 points, 4. Durability test results are included in thecategory of average, based on the mean value of 38.865 ml/kg/min, 5. PB Surya Baja Surabaya in reachingachievement, it is evident that the PB Surya Baja Surabaya has gained 43 medals over the past three years.Keywords : Badminton, Height, leg muscle explosive power, agility, Endurance, PB Surya BajaSurabaya Badminton Athletes Age 12-16 Years